Kappa-Casein Genotypic Frequencies in Holstein-Friesian Dairy Cattle in West Java Province - A Anggraini; C Sumantri; A Farajallah; E Andreas (Media Peternakan, 2010)
Kappa casein (ĸ-cn) gene as one of the four casein genes commonly has two variant alleles. B allele is positively correlated with milk proteins, so potentially be used as MAS to improve milk protein content. This study aimed to identify genetic variation of the ĸ-casein gene in Holstein-Friesian (HF) from several dairy regions in West Java. Blood samples were taken through jugular vein of lactating heifers and cows, from intensive managements under the Local Government Dairy Breeding Station - Cikole (BBPT Cikole-SP) (82 hds), Embryo Transfer Station (BET) (50 hds), and Eco Farm of Animal Science Faculty of Bogor Agricultural University (EcoFarm) (20 hds); as well as from semi-intensive managements of small dairy farmers under the supervision of the North Lembang Cooperative Unit (KPSBU Lembang) in two villages of Cilumber (98 hds) and Pasar Kemis (92 hds).  Blood samples were also taken via cocsigalis vein of AI (active and non active) HF bulls at the two National AI Stations in Lembang (25 hds) and Singosari (32 hds).  Identification of genetic variation was by applying PCR-RFLP method. Three genotypes were identified, namely AA, AB, and BB, resulting two alleles of A and B. Results entirely showed that the frequencies of the BB HF female were very low, with the range of 0%-6% (vs AA genotype= 10%-54% and AB genotype= 46%-85%), despite of the relatively high frequency of the B allele over the A allele (23%-48% vs. 52%-77%). The low frequency of the observed BB females might be due to the limited AI active BB bulls used for services by the two national AI stations (0%-4%).